A Production systems study on Philippine Glass Bulbs Inc. (PGB) - Deymata, Sylma Joy; Laroya, Cristina; Palaca, Henry; Te, Dennis (College of Engineering, 1994)
The study conducted in Philippine Glass Bulbs, makers of bulbs and tubes, was a follow up evaluation of a previous study made by IE 151 students during the SY '87-88. It was found out that some of the recommendations lack concrete analysis and evidence for them to be considered by the company for implementation The biggest problem encountered by the study group is the company's inability to meet demand and apparently (from the stream diagram) the management's lack of vision and enthusiasm. This lack of vision inhibits them from investing in a more efficient machinery fir production. Given the monetary constraints, the study group has opted to recommend alternatives which does not require a very big cash outlay. Among the study's alternatives with this problem is the total overhaul of the factory floor if they intend to remain in business for years to come. This alternative will part of a long range plan for the company. But this alternative has been scrapped because it will require a cash outlay of more than P/100M, therefore, this alternative is out of the question for the company. Recommendations were made regarding warehousing, working environment, maintenance and ways of improving production.